The new class - Brooke, Lauren (New York : Scholastic, 2005)
When Dylan Walsh arrives at Chestnut Hill, an exclusive boarding school in Virginia which emphasizes horsemanship, she realizes that her success will depend on the friends she makes.
008-013.
890
Accelerated Reader AR
Keywords: Boarding schools -- Virginia -- Juvenile fiction; Friendship -- Juvenile fiction; Horsemanship -- Juvenile fiction; Virginia -- Juvenile fiction